PENGARUH MODEL PROJECT BASED LEARNING (PjBL) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS IV SDN 101776 SAMPALI - Indah Novita; Nurhairani; Wildansyah Lubis; Imelda Free Unita Manurung; Waliyul Maulana Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to examine the effect of the Project Based Learning (PjBL) model on the creative thinking skills of fourth-grade students at SDN 101776 Sampali in the 2025/2026 academic year. This study employed a quantitative approach using a quasi-experimental research design, specifically the Pretest-Posttest Control Group Design. The research sample consisted of 60 students, including 30 students from Class IV A as the experimental group and 30 students from Class IV B as the control group. Data were collected using an essay test designed to measure students' creative thinking skills. Data analysis was conducted through normality testing, homogeneity testing, and hypothesis testing using the Independent Sample t-Test. The results showed that the data were normally distributed based on the Shapiro-Wilk test, with posttest significance values of 0.503 for the experimental group and 0.204 for the control group (> 0.05). The homogeneity test indicated a significance value of 0.138 (> 0.05), demonstrating that the variances of the two groups were homogeneous. Furthermore, the hypothesis testing using the Independent Sample t-Test yielded a significance value (2-tailed) of < 0.001 < 0.05, indicating that Ha was accepted and H₀ was rejected. Therefore, the findings of this study revealed that the Project Based Learning (PjBL) model was more effective than the Cooperative Learning model in improving students' creative thinking skills.